Characteristics of the Zooplankton Community Structure in Shengjin Lake and Its Response to the Restored Aquatic Vegetation - Dagne Tafa Dibar; Kun Zhang; Zhongze Zhou (Limnological Review, 2025)
Macrophytes taxa composition determines microinvertebrates utilized as environmental indicators in freshwater ecosystems. This study was conducted in Shengjin Lake. In this lake, local communities have been practicing using sine fishing nets for fishing and this has a disrupting effect on macrophyte vegetation, even though it was the major for the disappearance of submerged vegetation before it was banned. As a result of this sine fishing net ban by the local authorities, the vegetation that had disappeared began to recover. Thus, this study investigated the role of architecturally differentiated macrophytes restoration effect on zooplankton communities’ diversity, abundance, and species composition; open water was used as a control. For this, the data were collected from different habitats via site 1 (open water) site 2, (free-floating), site 3 (emergent and submerged), site 4 (submerged), and site 5 (emergent) macrophytes. In the present study, the results demonstrated that the relative mean density of Rotifer was measured high which ranged from (219 ± 141–678 ± 401 ind L−1), mainly dominated by Keratella cochlearis and Lecane cornuta species. Following Rotifera, Cladocera population density was reported high and ranged within (36 ± 6.2–262.5 ± 49.4 ind L−1). The Cladocera group was dominated by Daphnia spp., Moina micura, Ceriodaphnia reticulata, and Chydorus latus species. Compared to Rotifer and Cladocera, Copepod community were recoded least with relative mean density ranged within (11.52 ± 2.22–85.5 ± 27 ind L−1) and dominated by Microcyclops javanus, Thermodiaptomus galebi, and Sinocalanus doerrii species. From environmental variables and the zooplankton density relationship analyzed, the redundancy analysis (RDA) results indicated that Water Temperature, Chlorophyll a, Dissolved Oxygen, Total Phosphorus, and Ammonium Nitrogen were found the most influential variables on zooplankton communities. Stepwise regression correlation showed that Copepod and Cladocera were found more dependent on environmental ...